Experimental Determination of Computed Tomography Settings for Jaw Scanning - Adaskevicius, R.; Macianskytė, D.; Monastyreckiene, E. (Elektronika ir Elektrotechnika, 2011)
Aim of our study is to develop a method for the experimental identification of the settings of a computed tomography (CT) scanner used for scanning of human jaw. I this case, CT can be used for rapid prototyping of human jaw, design and manufacture of implants. The experimental identification of settings of a computed tomography scanner is done by comparing 3D computer models built using different data acquisition technologies: CT scanner and 3D laser scanner. The modified Iterative Closest Points algorithm is used for alignment of 3D computer models, obtained using different scanning methods. The different test objects were scanned using a spiral CT scanner and 3D laser scanner for testing the method. 3D computer models were compared uding the mean square value of distance between two surfaces. The test results indicate hardware and software parameters impacting on the accuracy and surface quality of 3D computer model reconstructed from CT data. Ill. 5, bibl. 7 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.373